2023
DOI: 10.3389/fimmu.2023.1244250
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes in patients with primary immunodeficiency diseases in Japan: baseline results from a prospective observational study

Hirokazu Kanegane,
Masataka Ishimura,
Toshinao Kawai
et al.

Abstract: IntroductionPrimary immunodeficiency diseases (PIDs) are rare inherited diseases resulting in impaired immunity. People with PID experience lower health-related quality of life (HR-QOL) and disease-related burdens in daily activities. This ongoing, prospective observational study aims to evaluate disease activity, treatment status, treatment-related burden, daily activities, and HR-QOL in patients with PID in Japan over a 1-year period. In this interim report (database lock: July 29, 2022), we present baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In our study, PID parents showed higher depression, state anxiety, and trait anxiety scores, along with increased fatigue. Untreated depression and anxiety can impair economic productivity, work and social functioning, relationships, physical health, and caregivers' problem‐solving abilities, ultimately impacting their HRQOL negatively 23 . Previous research focusing on parents of children with SCID, 9,22,24 and CGD 10 has demonstrated that HRQOL is inferior compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, PID parents showed higher depression, state anxiety, and trait anxiety scores, along with increased fatigue. Untreated depression and anxiety can impair economic productivity, work and social functioning, relationships, physical health, and caregivers' problem‐solving abilities, ultimately impacting their HRQOL negatively 23 . Previous research focusing on parents of children with SCID, 9,22,24 and CGD 10 has demonstrated that HRQOL is inferior compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Untreated depression and anxiety can impair economic productivity, work and social functioning, relationships, physical health, and caregivers' problem-solving abilities, ultimately impacting their HRQOL negatively. 23 Previous research focusing on parents of children with SCID, 9,22,24 and CGD 10 has demonstrated that HRQOL is inferior compared to the general population. Parents indicated that their foremost concerns about their children's PID were the enduring nature of the illness, its manageability, and the potential side effects of treatment.…”
Section: Ta B L Ementioning
confidence: 99%
“…Patients with chronic diseases, such as PID, are vulnerable to significant disease burden that can negatively impact their physical function, emotional well-being, work productivity, social interactions, and family life [ 10 16 ]. Regular long-term treatment regimens can impose a treatment-related burden that interferes with daily life, increases the risk of adverse events, and acts as a constant reminder of the disease [ 10 , 16 21 ]. Reduced treatment complexity and length of procedure has been shown to decrease treatment burden and have a positive impact on patient compliance and overall quality of life (QoL) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%